2014
DOI: 10.1111/1365-2664.12192
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability of moorland plant communities to environmental change: consequences of realistic species loss on functional diversity

Abstract: Summary1. Understanding the consequences of realistic species loss on the functioning and persistence of vulnerable ecosystems is key to devising conservation strategies when environmental changes are immediate threats. Yet, few studies have provided direct evidence for conservation prioritization and decision-making. 2. We incorporated the quantification of functional diversity based on the Rao index of diversity (FD rao ) into this applied context and examined the consequences of realistic species loss on fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 44 publications
(162 reference statements)
1
58
0
Order By: Relevance
“…In support of this idea, Yamada et al (2011) concluded that the functional diversity of the macrocrustacean community in seagrass ecosystems is the variable at the local patch scale, but homogeneous (i.e., occurrence of functional redundancy) at the regional scale (e.g. Matsuzaki et al, 2013;Sasaki et al, 2014).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In support of this idea, Yamada et al (2011) concluded that the functional diversity of the macrocrustacean community in seagrass ecosystems is the variable at the local patch scale, but homogeneous (i.e., occurrence of functional redundancy) at the regional scale (e.g. Matsuzaki et al, 2013;Sasaki et al, 2014).…”
Section: Discussionmentioning
confidence: 96%
“…By using groups and diversity based on ecological traits, i.e., ''functional group'' and ''functional diversity'', that is the value and range of functional traits and ecosystem function of organisms present in a community (e.g., Mouillot et al, 2013;Storkey et al, 2013), can lead to elucidate community assembly rules and/or ecosystem processes (Yamada et al, 2011;Matsuzaki et al, 2013;Sasaki et al, 2014). Functional diversity was measured based on the values and range of ecological traits of species such as microhabitat, dispersal ability, habitat type, life history, and trophic level (e.g., Schleuter and Daufresne, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…; Matsuzaki, Sasaki & Akasaka ; Sasaki et al . ). In a changing environment, this measure provides three major advantages: (i) valuable information on how river ecosystems respond to human and natural environmental stressors, which can help managing the current increase of multiple stressors across the river network, (ii) assessment of stressors’ effects on functional features from the descriptive to the predictive (being the assessment framework of broad‐scale applicability across ecological domains) and (iii) the geographical distribution of sites that potentially could show more stability, resistance and resilience, and vice versa.…”
Section: Discussionmentioning
confidence: 97%
“…Each plot includes the correlation between the two distances (q), the significance of Mantel test, and a lowess regression to illustrate the relationship. Redundancy can also be used in combination with nested subset analyses to estimate the vulnerability of ecosystem function to species loss (Zavaleta and Hulvey 2004, Sasaki et al 2014). (d) Changes in functional redundancy (expressed in relative terms) for single and multiple traits along the soil water content gradient.…”
Section: Discussionmentioning
confidence: 99%